2015
DOI: 10.1039/c4an01864h
|View full text |Cite
|
Sign up to set email alerts
|

Plasma biomarkers of pulmonary hypertension identified by Fourier transform infrared spectroscopy and principal component analysis

Abstract: The main goal of this study was to find specific plasma spectral markers associated with pulmonary arterial hypertension (PAH) induced by monocrotaline injection in rats. FTIR was used to monitor biochemical changes in plasma caused by PAH as compared with the systemic hypertension induced by partial ligation on the left artery and with the control group. Both pathologies, systemic and pulmonary hypertension, induced a unique response in the biochemical content of plasma, mainly related to the composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…As PER 10 mg/kg, but not PER 2 mg/kg, improved endothelial function the unsaturation level of plasma fatty acids seemed to reflect endothelial status, and most likely oxidative stress. Interestingly, our analysis of systemic and pulmonary hypertensions indicated a similar decrease of lipid unsaturation level in plasma that could also be relevant to the presence of endothelial dysfunction in these diseases [25,27].…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…As PER 10 mg/kg, but not PER 2 mg/kg, improved endothelial function the unsaturation level of plasma fatty acids seemed to reflect endothelial status, and most likely oxidative stress. Interestingly, our analysis of systemic and pulmonary hypertensions indicated a similar decrease of lipid unsaturation level in plasma that could also be relevant to the presence of endothelial dysfunction in these diseases [25,27].…”
Section: Resultssupporting
confidence: 57%
“…In summary, our results demonstrated that the combination of chemometric analysis and FTIR spectroscopic signature of the macromolecular vibrations found in 0.5 μL dried plasma films reflected closely metabolic disturbances of diabetes and can possibly be used for a rapid monitoring the metabolic response of the diabetes treatment . However, in contrast to other pathologies, in which pattern of FTIR plasma changes seemed to clearly reflect vascular wall pathology, for example, in NO‐deficient mice or pulmonary hypertension , and could be possibly used for monitoring of vasoprotective treatment, FTIR spectra in diabetes were dominated by massive diabetes‐related metabolical dysfunction that masks and overweighs the subtle endothelial‐related effects. However, in each of these 3 pathologies such as systemic hypertension, pulmonary hypertension and diabetes that are linked to endothelial dysfunction, alterations in the secondary structure of proteins are visible, suggesting that this type of changes may indeed constitute the reliable FTIR‐based fingerprint of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The IR spectrum contains rich and specific information about the molecular composition of the human serum which, coupled to advanced multivariate analysis tools, could deliver accurate diagnostics. Recent systematic studies have demonstrated the potential of IR serum based diagnosis with different data mining approaches such as Principal Components Analysis (PCA), PCA coupled to Linear Discriminant Analysis (PCA-LDA), Random Forest or Support Vector Machine (SVM) [26][27][28][29][30] . However, the development of spectroscopic technologies with medical perspectives needs to align with clinical requirements to enable clinical translation of these promising technologies 31 .…”
Section: Introductionmentioning
confidence: 99%